Reversibility of the Martensitic Transformations and Shape-Memory Effects - Lobodyuk, V.A. (Успехи физики металлов, 2016)
The results of the investigations of main peculiarities and reversibility of the martensitic transformations in different materials are considered and discussed. So unusual mechanical properties as shape memory effect, superelasticity, superplasticity and others phenomena caused by these transitions are also analyzed. The values of the recovering deformation are defined by the mechanism of the martensitic transformations and its reversibility. Reasons for their differences in the alloys with different character of the martensitic transition are also discussed.